Bed Spaces Management System for the Libyan Public Hospital Al-Jumhouriya in Benghazi - Abuzeid, Tarek M. (2011)
Recently, the online services have used widely in different fields for providing and facilitating user needs. Most of these services give the flexibility and easy to access anytime and anywhere without need to waste the time. This study was initialed for the current issues in determining the bed availability in the Libyan public hospital Al-Jumhouriya in Benghazi for pregnant. Thus, this study successful designed and developed the system based on the System Research Process Methodology. The system was developed based on JSP and MySQL tools and tested on local server. The result of the evolution found that the proposed Bed Reservation System (BRS) was easy to use, useful and achieve the uses intention in using it.